THE RELATIONSHIP BETWEEN SECONDARY SCHOOL TEACHERS’ ORGANIZATIONAL SUPPORT PERCEPTIONS AND THEIR ORGANIZATIONAL CYNICISM ATTITUDES - Gökyer, Necmi; Türkoğlu, İsmail (My University, 2018)
This study aims to identify the relationship between secondary school teachers’ organizationalsupport perceptions and their organizational cynicism attitudes. The population of this relationalsurvey included 1,602 teachers who were working at the 55 secondary schools located in centralElazig during the 2016-2017 school year. A total of 389 teachers working at 13 randomly selectedschools from among these were distributed the data collection tool. However, tools from only 319teachers were ultimately analyzed. The results showed that secondary school teachers agreed withthe organizational support and justice and organizational ownership sub dimensions and the entirescale, while they partially agreed with the personal and professional development sub dimension.The organizational support perceptions of teachers who did not consider leaving their schools werehigher than those who were considering or partly considering leaving. Teachers’ organizationalcynicism levels manifested at the highest level in the behavioral domain, followed by the cognitiveand affective domains.
Keywords: Eğitim; Eğitim Araştırmaları; Psikoloji